2021
DOI: 10.3389/fpls.2021.644010
|View full text |Cite
|
Sign up to set email alerts
|

Water Use, Leaf Cooling and Carbon Assimilation Efficiency of Heat Resistant Common Beans Evaluated in Western Amazonia

Abstract: In our study, we analyzed 30years of climatological data revealing the bean production risks for Western Amazonia. Climatological profiling showed high daytime and nighttime temperatures combined with high relative humidity and low vapor pressure deficit. Our understanding of the target environment allows us to select trait combinations for reaching higher yields in Amazonian acid soils. Our research was conducted using 64 bean lines with different genetic backgrounds. In high temperatures, we identified three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 79 publications
1
28
0
Order By: Relevance
“…For each slide reading, two random counts were made to determine the density of stomata (number mm 2 ). Likewise, the number of days to flowering (DF) and days to physiological maturity (DPM), as well as pollen viability (PV), as described by Suárez et al [ 10 , 19 , 34 ], were measured in order to determine the effects on phenological traits of different tepary accessions. The leaf temperature differential (LTD) corresponding to the difference between leaf and ambient temperature was measured using the MultispeQ handheld device [ 88 ] (Lansing, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each slide reading, two random counts were made to determine the density of stomata (number mm 2 ). Likewise, the number of days to flowering (DF) and days to physiological maturity (DPM), as well as pollen viability (PV), as described by Suárez et al [ 10 , 19 , 34 ], were measured in order to determine the effects on phenological traits of different tepary accessions. The leaf temperature differential (LTD) corresponding to the difference between leaf and ambient temperature was measured using the MultispeQ handheld device [ 88 ] (Lansing, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Latin American region alone accounts for 40% of acidic soils worldwide, which represents a limitation for common bean cultivation [ 33 ]. In the Amazon region, the adaptation of advanced lines of common bean under acid soils with low fertility and high temperature conditions has been studied [ 10 , 19 , 34 ] to identify materials with adaptability, thus being able to improve the diet of small farmers in rural areas. However, the available germplasm collection of Phaseolus acutifolius accessions was not evaluated to identify materials that can adapt to the combined stress of high temperature and low fertility acid soils with high aluminum (Al) toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, climatic conditions (high air humidity, high rainfall and high air temperature) in the Amazon region were favorable for the more frequent development of diseases. However, in the previous studies conducted by Suárez et al [ 48 , 59 , 60 ], we identified bean lines that were adapted to abiotic stress conditions at the physiological level and these lines produced grain yields that were above the Colombian average yield.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, an increase in Y(NO) was detected at the expense of a decrease in NPQ condition, as was also observed by Suárez at el. [ 48 ]. These observed changes are possibly attributable to irreversible damage in the PSII reaction centers due to the infection process, and they resulted in possible photoinhibition as reflected by low F v /F m levels [ 49 ].…”
Section: Discussionmentioning
confidence: 99%